As máscaras em Luigi Pirandello: aproximações pontuais com Nietzsche - Gaspar, Jean Fabian Daud (2012)
In this dissertation, we will analyze the work of Luigi Pirandello and his involvement with the masks problematic having as horizon possible similarities and differences with the writings of philosopher Friedrich Nietzsche. Being this objective of the present work, we will try to draw a parallel, initially between the ancient tragedy and modern, reflecting the disharmony with Pirandello on the subject and, with Nietzsche in certain specific criticisms of the alleged unity of the subject. Along the way, will emerge, differentially, the themes of the suffering of the individual, the "I" multiple and misfit of the subject that will support, along with the "conscience" of multiplicity, for a finding of coherence waving to the masks